2020
DOI: 10.1558/jmtp.15517
|View full text |Cite
|
Sign up to set email alerts
|

Does bilingualism correlate with or predict higher proficiency in L3 English? A contrastive study of monolingual and bilingual learners

Abstract: This study investigates whether English in instructed settings is more successfully acquired by learners who are already bilingual in comparison to those with a monolingual background. There remains substantial controversy regarding potential advantages of bilingual speakers in their acquisition of additional languages, especially in heritage speaker contexts. We here contribute to this discussion by analysing the English C-test results of 1,718 bilingual and monolingual students of grades 7 and 9, sampled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…more lexical transfer bases), but also to conceptual knowledge and more general cognitive skills like executive control or higher metalinguistic awareness in bilinguals (see Section 1). Our findings are thus in line with previous research that casted doubt on a general bilingual advantage, at least in heritage speaker contexts (see Berthele and Udry 2019;Berthele and Vanhove 2020;Lorenz et al 2020 for similar results).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…more lexical transfer bases), but also to conceptual knowledge and more general cognitive skills like executive control or higher metalinguistic awareness in bilinguals (see Section 1). Our findings are thus in line with previous research that casted doubt on a general bilingual advantage, at least in heritage speaker contexts (see Berthele and Udry 2019;Berthele and Vanhove 2020;Lorenz et al 2020 for similar results).…”
Section: Discussionsupporting
confidence: 93%
“…However, the outcomes of studies dealing with a proposed "multilingual boost effect" (Berthele and Udry 2019) in L3 acquisition by heritage bilinguals are again far from being unequivocal. While some studies on the acquisition of English or Romance foreign languages at school yielded supportive evidence for a bilingual advantage, others did not (see Lorenz et al 2020 for a recent overview). In light of this confusing picture, our contribution provides new evidence on potential bilingual advantages in contexts of additional language learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also studies that found no differences between monolingual and bilingual FL learners (Jaspaert and Lemmens, 1990;Sanders and Meijers, 1995;Schoonen et al, 2002;Edele et al, 2018;Zoutenbier and Zwitserlood, 2019;Lorenz et al, 2020), or even found that bilinguals were outperformed by their monolingual peers (Van Gelderen et al, 2003). For instance, Jaspaert and Lemmens (1990) measured L3 Dutch proficiency of Italian-French immigrant bilinguals in Brussels and compared it to that of French monolinguals.…”
Section: Open Accessmentioning
confidence: 99%
“…Bilingual benefits are also more likely to be found in additive contexts (where both first languages are maintained, as in Spain or Canada) than in subtractive contexts (where L2 is acquired at the expense of L1) (Cummins, 2000). Other relevant factors that have been proposed in the literature to explain the controversial findings include typological proximity between L3 and the previously acquired languages (Swain et al, 1990;Schepens et al, 2016), levels of bilingual proficiency (Lasagabaster, 2000;Muñoz, 2000;Sagasta Errasti, 2003;Edele et al, 2018;Lorenz et al, 2020), language use in the home (Maluch et al, 2016), code-switching practices (Maluch and Kempert, 2017) and literacy in the home language (Swain et al, 1990;Keshavarz and Astaneh, 2004;Rauch et al, 2011).…”
Section: Bilingual Fl Learning Advantages In Pupils With Typical Lang...mentioning
confidence: 99%
“…There is some research examining this question with children learning a foreign language in a non-immersion educational context. Lorenz et al (2020) reported no difference in the acquisition of English by monolingual (second language) and bilingual (third language) adolescents in Germany, but potential cultural and socioeconomic differences may have impacted results. Little information was provided regarding parental education, parental proficiency in English, or interaction with the English language outside of the classroom, and it is possible that there were socioeconomic differences between the language groups.…”
mentioning
confidence: 91%